Pixel-by-pixel precise delay correction for measurement of cerebral hemodynamic parameters in H(2)(15)O PET study - Islam, Muhammad M. (Ann Nucl Med, 2017)
OBJECTIVE: A new method of delay time estimation was proposed to measure precise cerebral blood flow (CBF) and arterial-to-capillary blood volume (V (0)) using (15)O-water PET. METHODS: Nineteen patients with unilateral arterial stenoocclusive lesions were studied to evaluate hemodynamic status before treatment. The delay time of each pixel was calculated using least squares fitting with an arterial blood input curve adjusted to the internal carotid artery counts at the skull base. Pixel-by-pixel delay estimation provided a delay map image that could be used for precise calculation of CBF and V (0) using a one-tissue compartment model, and the values from this method were compared with those from the slice-by-slice correction method. RESULTS: The affected side showed a longer delay time than the contralateral cerebral hemisphere. Although the mean cortical CBF values were not different between the two methods, the slice-by-slice delay correction overestimated CBF in the hypo perfused area. The scatter plot of V (0) pixel values showed significant difference between the two correction methods where the slice-by-slice delay correction significantly overestimated V (0) in the whole brain (P < 0.05). CONCLUSION: Pixel-by-pixel delay correction provides delay images as well as better estimation of CBF and V (0), thus offering useful and beneficial information for the treatment of cerebrovascular disease.